2020
DOI: 10.1002/chem.202001970
|View full text |Cite
|
Sign up to set email alerts
|

Boron Effect on Sugar‐Based Organogelators

Abstract: The reaction of several alkylglucosides with phenyl boronic acid permittede asya ccess to as eries of alkylglucoside phenyl boronate derivatives. This type of compound has structures similar to those of known benzylidene glucoside organogelators except for the presence of ab oronate functioni np lace of the acetalo ne. Low to very low concentrationso ft hese amphiphilic molecules produced gelation of several organic solvents. The rheological properties of the correspondings oft materials characterizedt hem as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 57 publications
(21 reference statements)
1
20
0
Order By: Relevance
“…Overall, the study shows that the alkyl chain length only influenced gelation at the microscopic level, but the substituents on the aniline ring affected the stability and self-assembly of the gels [43]. Ludwig et al reported a water-sensitive organogelator that is structurally similar to the successful 4,6-benzylidene protected alkyl glucoside derivatives that have been shown to be effective organogelators ( Figure 5) [44]. The resulting phenyl boronic protected alkyl glucoside derivatives 12a-h were found to be effective gelators for toluene, cyclohexane, ethyl myristate and isopropyl palmitate.…”
Section: D-glucose Derivatives As Lmwgsmentioning
confidence: 96%
See 4 more Smart Citations
“…Overall, the study shows that the alkyl chain length only influenced gelation at the microscopic level, but the substituents on the aniline ring affected the stability and self-assembly of the gels [43]. Ludwig et al reported a water-sensitive organogelator that is structurally similar to the successful 4,6-benzylidene protected alkyl glucoside derivatives that have been shown to be effective organogelators ( Figure 5) [44]. The resulting phenyl boronic protected alkyl glucoside derivatives 12a-h were found to be effective gelators for toluene, cyclohexane, ethyl myristate and isopropyl palmitate.…”
Section: D-glucose Derivatives As Lmwgsmentioning
confidence: 96%
“…Ludwig et al reported a water-sensitive organogelator that is structurally similar to the successful 4,6-benzylidene protected alkyl glucoside derivatives that have been shown to be effective organogelators ( Figure 5 ) [ 44 ]. The resulting phenyl boronic protected alkyl glucoside derivatives 12a–h were found to be effective gelators for toluene, cyclohexane, ethyl myristate and isopropyl palmitate.…”
Section: Structure and Gelation Properties Of Monosaccharide Derivmentioning
confidence: 99%
See 3 more Smart Citations